Picturesque Trinidad - Rice, Ben (My University, 2010)
The trees in the foreground appears to be Poui, while those in the background are Saman, a species of flowering tree with a wide canopy.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Savannas--Trinidad and Tobago; [1911]; Cities and towns--Trinidad and Tobago--Port of Spain; Queen's Park Savannah (Port of Spain)